[Letter from A. Phillip Randolph Institute opposing excise tax] (Tufts Archival Research Center, 2007)
Letter from the A. Philip Randolph Institute to a U.S. congressman discussing a raise in the tobacco excise tax. Expresses opposition to the tax due to the possibility of creating unemployment in the tobacco and related industries. Fears that the tax will be felt regressively and that it will be an unreliable source of income to be used towards health care reform.